Determinants of Shariah Control Deficiencies: an Indonesian Shariah Banking Perspective - Edi Sutanto; Amilin Amilin; Ibnu Qizam; Erika Amelia (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2025)
This study aims to identify patterns of deficiency in the Shariah Internal Control System (SICS) and uncover determinant factors of Shariah Control Weakness (SCW) in Indonesian Islamic commercial banks. Using an embedded multiple-case study approach, the research combines analysis of financial and governance reports from Islamic banks for 2013–2024 period with interviews with ten Islamic banking practitioners. The findings reveal that Shariah Non-Compliance Events (SNCE) occur systemically across all observed banks, with deficiency patterns including non-halal income, Shariah audit findings, and fraud, and identified 12 determinant factors for SCW, which are the control weakness, poor employee understanding of Shariah, pressure from customers and business targets, complexity of akad, the number, quality & meeting frequency of Shariah Supervisory Board members, number of branch offices, employee training budget, bank's total assets, and the bank's age. Keywords: shariah banking, shariah governance, shariah compliance: shariah internal control system; sharia control weakness Abstrak Penelitian ini bertujuan mengidentifikasi pola defisiensi dalam Sistem Pengendalian Internal Syariah dan faktor determinan kelemahan pengendalian syariah (SCW) pada bank umum syariah di Indonesia. Menggunakan pendekatan embedded multiple-case study, penelitian ini mengombinasikan analisis laporan keuangan dan tata kelola bank syariah periode 2013–2024 dengan wawancara terhadap sepuluh praktisi perbankan syariah. Penelitian menyimpulkan bahwa ketidakpatuhan syariah terjadi secara sistemik di seluruh bank yang diteliti, dengan pola defisiensi berupa pendapatan non-halal, temuan audit syariah, dan fraud, serta adanya 12 faktor determinan SCW, yaitu kelemahan pengendalian, pemahaman syariah pegawai yang minim, tekanan nasabah & capaian target, kompleksitas akad, jumlah, frekuensi pertemuan & kualitas DPS, jumlah kantor cabang, anggaran pelatihan pegawai, kuantitas aset bank, dan lamanya bank beroperasi. Kata Kunci: shariah compliance: shariah internal control system; sharia control weakness